2020
DOI: 10.1098/rsos.200058
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and weathering mechanisms of the traditional Chinese blue brick from the ancient city of Ping Yao

Abstract: The traditional blue brick was the dominant clay brick used in Chinese architecture before the mid-nineteenth century. The ancient city of Ping Yao, a United Nations Educational, Scientific and Cultural Organization (UNESCO) heritage site, is an outstanding example of blue brick architecture. The Ping Yao bricks within the damp areas (up to 4 m at highest) of the ancient city's walls and private houses are subjected to various weathering, including contour scaling, flaking, powdering and salt crystallization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In the formula: ρ 0 is the apparent density of blue brick material, the unit is g/cm 3 . m is the mass of specimen under natural state, the unit is g. V is the volume of the specimen, the unit is cm 3 .…”
Section: Test Methods 221 Physical Properties Testmentioning
confidence: 99%
See 2 more Smart Citations
“…In the formula: ρ 0 is the apparent density of blue brick material, the unit is g/cm 3 . m is the mass of specimen under natural state, the unit is g. V is the volume of the specimen, the unit is cm 3 .…”
Section: Test Methods 221 Physical Properties Testmentioning
confidence: 99%
“…In the formula: P is the porosity of blue brick material, the unit is %. ρ 0 is the apparent density of blue brick material, the unit is g/cm 3 . ρ is specimen density, the unit is g/cm 3 .…”
Section: Test Methods 221 Physical Properties Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers have examined the characteristics of bricks under freezing and thawing environments, and have obtained a number of results. Liu and Zhang found that salt crystallization and freeze–thaw cycles were important factors leading to brick weathering through on-site investigations and indoor experiments, and formulated antiweathering strategies [ 10 ]. Tang et al studied the effects of freeze–thaw action and saturation on the mechanical properties of ancient bricks and mortar [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dynasties and regions had a particular influence on the composition of ancient bricks. To explore the main factors of the weathering of blue bricks in the ancient city of Pingyao, Liu et al 17 conducted various performance studies on the blue clay bricks in the old town of Pingyao. The results showed that the crystallization and freeze–thaw cycles of soluble salts were the two main factors leading to the weathering of these bricks.…”
Section: Introductionmentioning
confidence: 99%